2019
DOI: 10.1002/cmdc.201900021
|View full text |Cite
|
Sign up to set email alerts
|

Rational Adaptation of L3MBTL1 Inhibitors to Create Small‐Molecule Cbx7 Antagonists

Abstract: Chromobox homolog 7 (Cbx7) is an epigenetic modulator that is an important driver of multiple cancers. It is a methyl reader protein that operates by recognizing and binding to methylated lysine residues on specific partners. Herein we report our efforts to create low‐molecular‐weight inhibitors of Cbx7 by making rational structural adaptations to inhibitors of a different methyl reader protein, L3MBTL1, inhibitors that had previously been reported to be inactive against Cbx7. We evaluated each new inhibitor f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…abrogating the binding of CBX7 to INK4A/ARF loci in PCa cells. Simhadri et al (250) created a low-molecular-weight inhibitor of CBX7 (33F) via the rational modification of the structure of methyl-reading protein lethal 3 malignant brain tumor-like protein inhibitor 1. Denton et al (251) identified an effective and selective inhibitory peptide, PSL, against CBX7 and CBX8 and confirmed that the acylation of this inhibitory peptide by 5-methylisoxazole-3-carboxylic acid (PSL-81) increased the potency and selectivity of CBX8.…”
Section: Cancer Therapies Targeting Cbxsmentioning
confidence: 99%
“…abrogating the binding of CBX7 to INK4A/ARF loci in PCa cells. Simhadri et al (250) created a low-molecular-weight inhibitor of CBX7 (33F) via the rational modification of the structure of methyl-reading protein lethal 3 malignant brain tumor-like protein inhibitor 1. Denton et al (251) identified an effective and selective inhibitory peptide, PSL, against CBX7 and CBX8 and confirmed that the acylation of this inhibitory peptide by 5-methylisoxazole-3-carboxylic acid (PSL-81) increased the potency and selectivity of CBX8.…”
Section: Cancer Therapies Targeting Cbxsmentioning
confidence: 99%
“…A set of small molecule inhibitors with low potency developed by rational adaption of inhibitors of L3MBTL1, a methyllysine-binding protein ( 285 ). This work identified multiple small-molecule inhibitors with modest to low potency (IC 50 : 257–500 μM).…”
Section: Polycomb Group Protein Modulators: Inhibitors/ Degraders/ Activatorsmentioning
confidence: 99%
“…[20] Recent efforts also included PROTACs, [ 21 , 22 ] that might help to address non-catalytic functions of PRC2 as observed in the synthetic lethal relationship with BAF complex deletions. [23] Efforts to generate small molecule inhibitors for the CBX family have so far also focused on CBX6, 7, and 8 [24][25][26][27][28][29][30] , with varying degrees of success at achieving selectivity. [31] Further elucidation of the PRC1 complex function and specifically CBX2, in NEPC would benefit from cell permeable and selective CBX2 tool molecules.…”
Section: Introductionmentioning
confidence: 99%